Creativity in the Age of Technology: Measuring the Digital Creativity of Millennials. Issue 2 (2nd April 2016) - Hoffmann, Jessica; Ivcevic, Zorana; Brackett, Marc
Abstract : Digital technology and its many uses form an emerging domain of creative expression for adolescents and young adults. To date, measures of self-reported creative behavior cover more traditional forms of creativity, including visual art, music, or writing, but do not include creativity in the digital domain. This article introduces a new measure, the Creative Behavior Questionnaire: Digital (CBQD), which assesses self-reported creative behavior in the digital domain. High school students ( N  = 230) completed the CBQD, as well as several other measures of creativity and personality. Factor analysis revealed 3 factors: digital creativity achievement, school-based everyday creativity, and self-expressive digital creativity. Factor-based scales showed expected correlations with other creativity measures, as well as Big-Five personality traits and Unconventionality, supporting construct validity. Results indicate that the CBQD can be used as an independent or a supplemental measure of creative behavior.